Utilization of coconut shells in the manufacture of appropriate goods - Ginting, Mimpin; Supeno, Minto (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Coconut shell inside is hard or very hard polymer, because of the composition of lignin > cellulose, such material s not good as a TV antenna. Because if given electromagnetic waves there will be vibrations of molecules >> ure rotation. To overcome this, the lignin concentration is reduced so that the concentration of lignin <cellulose can be used as a TV antenna, HP, because such material has become soft material. This combination of soft> hard polymers can theoretically be used for the purpose of detecting earthquakes, satellite etc. If the coconut is shaken, there will be ripples of coconut water to the ears, facts thus showing that the coconut shell has gaps or pores which carries waves of coconut water to the ears, which come out through the interface of lignin cellulose. The initial symptoms thus mean that the coconut shell can reflect and absorb waves. The advantages of this antenna can close up more clear, clear, cool clearer eyes and reception, can be used in the lowlands, highlands and at the bottom sea, this antenna is very good performance for high frequencies, can close up clearer, clear, cool in the eyes and voice reception clearer.